Features of information accounting and analysis on enterprises of tourism business - Kosenko, O. (My University, 2020)
The report states that operators conclude that in to advertising in regular media, Internet advertising is also required. Depending on the characteristics of the tour operator, Internet advertising can pursue different goals: creating a favorable image of the company in the market; promotion of new tourist destinations; increase in sales of own tourist product; stimulating travel of the agency to work with this tour operator; to stimulate the final consumer - the tourist to buy in the authorized agencies products of this tour operator, instead of its competitors.
Особливості обліку та аналізу інформації на підприємствах туристичного бізнесу
Keywords: Internet advertising; efficiency; frequency; costs; travel business